2015
DOI: 10.1007/s11130-015-0516-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Addition of Amaranth (Amaranthus mantegazzianus) Protein Isolate on Antioxidant Status, Lipid Profiles and Blood Pressure of Rats

Abstract: The effects of the dietary addition of 2.5% (w/w) Amaranthus mantegazzianus protein isolate (AI) on blood pressure, lipid profiles and antioxidative status of Wistar rats were evaluated. Six diets were used to feed animals during 28 days: (base (AIN93G), Chol (cholesterol 1%, w/w), CE (α-tocopherol 0.005%, w/w), CholE (cholesterol 1% (w/w) + α-tocopherol 0.005%, w/w), CAI (AI 2.5% w/w), CholAI (cholesterol 1% (w/w) + AI 2.5%, w/w). Lipid profiles of plasma and liver and faecal cholesterol content were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
2
20
0
6
Order By: Relevance
“…It has been reported that hamsters feed with amaranth protein was observed a 27% of hypercholesterolemia reduction, but when amaranth was administered in the presence of casein the observed reduction reached the 48% [22]. It was also reported that treated Wistar rats with 2.5% (w/w) of a protein isolate of Amaranthus mantegazzianus had a significant decrease in the plasma levels of CHO, TG, and oxidation when compared with control rats [23]. However, until date, no studies have been reported on the influence of amaranth on regulation of hormone profiles.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that hamsters feed with amaranth protein was observed a 27% of hypercholesterolemia reduction, but when amaranth was administered in the presence of casein the observed reduction reached the 48% [22]. It was also reported that treated Wistar rats with 2.5% (w/w) of a protein isolate of Amaranthus mantegazzianus had a significant decrease in the plasma levels of CHO, TG, and oxidation when compared with control rats [23]. However, until date, no studies have been reported on the influence of amaranth on regulation of hormone profiles.…”
Section: Discussionmentioning
confidence: 98%
“…The studies carried out by Lado et al. () and Escudero et al. () with Wistar rats with diets containing isolated or amaranth protein concentrates have been shown a modification of the lipid profile in animals, particularly in liver, and increases in the excretion of Cho in feces.…”
Section: Resultsmentioning
confidence: 93%
“…They are a very good source of healthy lipids, like unsaturated fatty acids, and bioactive compounds like tocopherols, squalene, and biopeptides, between others (Ogrodowska et al., ; Tovar‐Pérez, Lugo‐Radillo, & Aguilera‐Aguirre, ; Velarde‐Salcedo, Bojórquez‐Velázquez, & Barba de la Rosa, ). Different studies show that amaranth biopeptides in addition to presenting cho‐lowering activity, present antithrombotic, antioxidant, and antihypertensive activity, which is why they have a potential application in foods as a functional component (Chávez‐Jáuregui et al., ; Orsini‐Delgado et al., ; Lado, Burini, Rinaldi, Añón, & Tironi, ; Plate & Arêas, ; Quiroga, Aphalo, Nardo, & Añón, ; Sabbione, Rinaldi, Añón, & Scilingo, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations